2000
DOI: 10.1007/pl00000746
|View full text |Cite
|
Sign up to set email alerts
|

Expression and cellular distribution of perchloric acid-soluble protein is dependent on the cell-proliferating states of NRK-52E cells

Abstract: To clarify the biological role of kidney perchloric acid-soluble protein 1 (K-PSP1), its expression and intracellular distribution were examined in normal rat kidney epithelial NRK-52E cells. K-PSP1 expression was low during the proliferating phase and high in the stationary phase, and shown to have a negative relationship with the protein-synthesizing activity of the cells. Immunocytochemical studies revealed that K-PSP1 is predominantly located in the cytosol, especially in endoplasmic reticulum and Golgi ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Biological studies of its function suggest that it may play a role in cellular differentiation and development because levels are significantly increased during differentiation from human monocytes to macrophages (17) and during the development process of rat kidney, rat brain, pig liver, and chick liver (11,(18)(19)(20). Furthermore, expression of PSP depends on the proliferation states of the cell and overexpression of PSP reduces cell proliferation of normal rat kidney epithelial NRK-52E cells (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Biological studies of its function suggest that it may play a role in cellular differentiation and development because levels are significantly increased during differentiation from human monocytes to macrophages (17) and during the development process of rat kidney, rat brain, pig liver, and chick liver (11,(18)(19)(20). Furthermore, expression of PSP depends on the proliferation states of the cell and overexpression of PSP reduces cell proliferation of normal rat kidney epithelial NRK-52E cells (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…1) We have reported that PSP is related to cell proliferation and/or differentiation. [2][3][4][5] In fetal rat kidney, PSP was expressed in differentiated renal tubules but not in glomeruli. 2) In cultured cell lines, the expression of PSP was lower during the proliferation phase than during the confluent phase.…”
mentioning
confidence: 99%
“…2) In cultured cell lines, the expression of PSP was lower during the proliferation phase than during the confluent phase. 4) Overexpression of PSP inhibited cell proliferation in cultured cell lines. 5) In chick embryos, PSP is expressed in the neuroepithelial cells at embryonic day 3.…”
mentioning
confidence: 99%
See 2 more Smart Citations